Training in basic Internet skills for special target groups in non-formal educational settings - conclusions from three pilot projects - Berger , Andrea; Croll , Jutta (Research in Learning Technology, 2012)
With the progress of Digital Inclusion, it becomes important to address marginalised groups that face specific barriers in being part of the information society. From 2009 to 2011 within the framework of the nation-wide Initiative Internet erfahren, funded by the German Federal Ministry of Economics, Stiftung Digitale Chancen has accompanied three pilot projects and researched the hindrances and motivations of specific target groups including young migrants from Russia, women in the low-wage sector and disabled elderly people, regarding their use of information and communication technology and related skills. This article describes the teaching methodologies in the training provided in nonformal education settings, exposes the different evaluation methods and sums up the results. A special focus in the discussion is given to the role of the teacher and the relationship between teacher and students as there turned out to be similarities in all three target groups. Understanding the balance between the training and abilities and preferences of the learners will facilitate the further development of training appropriate to those who are still digitally excluded. Keywords: specific target groups in Digital Inclusion; migrants; disabled persons; low-wage sector; barriers towards formal education and technology; student motivation; trainer student relationship (Published: 19 December 2012) Citation: Research in Learning Technology 2012, 20: 18700 - http://dx.doi.org/10.3402/rlt.v20i0.18700